(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article highlights the parallel corpus and the approach of paremias in parallel corpora. In parallel corpuses, paremias are given on the basis of translation and comparable corpus. The corpus-based approach provides an opportunity to gain valuable insight about the distribution of paremias and their role in a language community We investigated paremias on the basis of the Russian National Corps and Sketch Engine corpora.